Chronic venous insufficiency: a review - Barajas Colón, José Ángel; Granados-Romero, Juan José; Barrera-Mera, Baltazar; Banegas-Ruiz, Rodrigo; Vargas-Morales, José Juan; Barrera-Calva, Elvira; Gómez-Mendoza, Francisco Fabián; Baca-Domínguez, Carlos Rubén; Jiménez Caprielova, Yuri; Pérez Ortega, Emilio; Mendoza-Aceves, Rodrigo A.; Abundez-Pliego, Ana Lilia; et al. (International Journal of Research in Medical Sciences, 2021)
Chronic venous insufficiency (CVI) comprises a complete spectrum of morphological and functional abnormalities of the venous system1 including any long-term functional and morphological alteration. CVI accounts for several abnormalities of the venous system. It is a highly prevalent disease that causes serious economic consequences, a decrease in the quality of life and can lead to serious complications. An exhaustive review was performed with the available literature, using the PubMed, ScienceDirect, Scopus and Cochrane databases from 2004 to 2021. The search criteria were formulated to identify reports related to chronic venous insufficiency. The pathophysiology of chronic venous insufficiency begins with chronic venous hypertension and the dilation of the vessel, this leads to a series of pathological changes in the venous wall and surrounding tissues, in advanced stages of CVI, skin lesions are associated with an increased proliferation of skin capillaries and microcirculatory abnormalities that may be the result of an altered level of factors responsible for the angiogenic response, such as vascular endothelial growth factor (VEGF), fibroblast growth factor 2 (FGF2) and angiostatin. In this review, updates on pathophysiology, clinic, diagnosis, classification and treatment of this disease are analyzed, with special emphasis on therapeutic options. Chronic venous insufficiency is a disease that affects the patient at several levels, mainly diminishing his/her quality of life. Currently there are various treatments ranging from habit modifications, pharmacological, to endovenous and surgical treatment.